Biological activity of T4 DNA synthesized in toluene-treated Escherichia coli cells. - McNicol, L A (1975)
T4 DNA synthesized in a toluene-treated cell system can act as the genetic donor in a DNA transformation assay. This material transforms a variety of markers at high efficiency. We present evidence that the genetic activity is due to newly synthesized, double-stranded DNA.